Development and perspectives of rapid detection technology in food and environment. Issue 17 (25th September 2022) - Jia, Xue-Xia; Li, Shuang; Han, Dian-Peng; Chen, Rui-peng; Yao, Zi-Yi; Ning, Bao-an; Gao, Zhi-Xian; Fan, Zhen-Chuan
Abstract: Food safety become a hot issue currently with globalization of food trade and food supply chains. Chemical pollution, microbial contamination and adulteration in food have attracted more attention worldwide. Contamination with antibiotics, estrogens and heavy metals in water environment and soil environment have also turn into an enormous threat to food safety. Traditional small-scale, long-term detection technologies have been unable to meet the current needs. In the monitoring process, rapid, convenient, accurate analysis and detection technologies have become the future development trend. We critically synthesizing the current knowledge of various rapid detection technology, and briefly touched upon the problem which still exist in research process. The review showed that the application of novel materials promotes the development of rapid detection technology, high-throughput and portability would be popular study directions in the future. Of course, the ultimate aim of the research is how to industrialization these technologies and apply to the market.